INTEGRAL PROTECTION OF CHILDREN AND ADOLESCENT AS A COLLECTIVE RIGHT BEFORE THE VIOLATION OF THE PRIVACY PRINCIPLE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This study aims to highlight the importance of protecting the privacy of children and adolescents. The principle of privacy aims to ensure the protection of intimacy, private life and image, given the consequences  that too much exposure generates in the individual and collective aspects. The research is classified as hypothetical-deductive, descriptive and bibliographic. The consecration of the Doctrine of Integral Protection and its importance in the recognition of children and adolescents as subjects of law stands out. The case of the ten-year-old child, a victim of rape and whose case gained the media when the discovery of pregnancy and the performance of legal abortion, with emphasis on media exposure, is presented. Fundamental rights are addressed, in particular privacy, as well as the administrative sanctions to which subject those who disclose data and information related to administrative, police or judicial procedures. It is demonstrated that the violation of privacy is not limited to individual damages, as it affects the whole society. It is concluded, therefore, that situations such as that of the girl from Espírito Santo, which culminate in unreasonable and irresponsible exposure, violate the principle of privacy, which is not limited to the authors of infringing acts, but gains prominence mainly in the case of sexual crimes , because it corroborates for stigmatization. Therefore, it is the duty of the State to effectively sanction those who disregard the legal precepts and expose the children and youth public, not limited to administrative sanctions, gaining relief, in that scenario, The civil liability for collective damages.Keywords: Child and Adolescent. Privacy. Fundamental rights. Violation. Individual and Collective Rights.